Intraoperative angiography imaging correlates with wound complications following soft tissue sarcoma resection. Issue 10 (20th January 2022) - Lazarides, Alexander L.; Saltzman, Eliana B.; Visgauss, Julia D.; Mithani, Suhail K.; Eward, William C.; Brigman, Brian E.
Abstract: For soft tissue sarcoma patients receiving preoperative radiation therapy, wound complications are common and potentially devastating. The purpose of this study was to assess the feasibility of intraoperative indocyanine green fluorescent angiography (ICGA) as a predictor of wound complications in these patients. A consecutive series of patients with soft tissue sarcoma of the extremities or pelvis who received neoadjuvant radiation and a subsequent radical resection received intraoperative ICGA with the SPY PHI device (Stryker Inc.) at the time of closure. Retrospective analysis of fluorescence signal along multiple points of the wound length was performed and quantified. The primary endpoint was wound complication, defined as delayed wound healing or wound dehiscence, within 3 months of surgery. Fourteen patients with preoperative irradiated soft tissue sarcoma were consecutively imaged. There were six patients with wound complications classified as "aseptic" in five cases. Using the ICGA, blinded surgeons correctly predicted wound complications in 75% of cases. During the inflow phase, a mean ratio of normal of 0.62 maximized the area under the curve (AUC = 0.90) for predicting wound complications with a sensitivity of 100% and specificity of 77.4%. During the peak phase, a mean ratio of normal of 0.55 maximized the AUC (0.95) for predicting wound complications with a sensitivity of 88.9% and a specificity of 100%. Intraoperative use of ICGA may help to predict wound complications in patients undergoing resection of preoperatively irradiated soft tissue sarcomas of the extremities and pelvis.